2020
DOI: 10.2147/jir.s229691
|View full text |Cite
|
Sign up to set email alerts
|

<p>Saturated Fatty Acids in Obesity-Associated Inflammation</p>

Abstract: Obesity is a major risk factor for the development of various pathological conditions including insulin resistance, diabetes, cardiovascular diseases, and non-alcoholic fatty liver disease (NAFLD). Central to these conditions is obesity-associated chronic low-grade inflammation in many tissues including adipose, liver, muscle, kidney, pancreas, and brain. There is increasing evidence that saturated fatty acids (SFAs) increase the phosphorylation of MAPKs, enhance the activation of transcription factors such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 147 publications
(192 reference statements)
4
77
0
4
Order By: Relevance
“…Substantial evidence has accumulated in recent years indicating that the ingestion of SFA increases innate immune activity resulting in both a postprandial and, with regular intake, chronic rise in pro-inflammatory mediators; see Zhou et al for a recent review. 22 Despite this, the association between the ingestion of SFA and the [Kyn]:[Trp] ratio, a marker of INF-γ mediated inflammatory processes, had not been previously reported. We therefore investigated, in an essentially healthy cohort, whether the intake of fatty acids and their percentage within the membrane influence the ratio of Kyn to Trp in plasma.…”
Section: Discussionmentioning
confidence: 98%
“…Substantial evidence has accumulated in recent years indicating that the ingestion of SFA increases innate immune activity resulting in both a postprandial and, with regular intake, chronic rise in pro-inflammatory mediators; see Zhou et al for a recent review. 22 Despite this, the association between the ingestion of SFA and the [Kyn]:[Trp] ratio, a marker of INF-γ mediated inflammatory processes, had not been previously reported. We therefore investigated, in an essentially healthy cohort, whether the intake of fatty acids and their percentage within the membrane influence the ratio of Kyn to Trp in plasma.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, cancer lipid profiles showed different findings in the degree of fatty acyl saturation in cancer patients [ 55 , 56 , 57 ]. We report decreased levels of circulatory saturated free fatty acids in the transition from healthy control to CLD and HCC patients that might be due to their role in activation of inflammatory cytokines [ 58 ]. Activation of the stearoyl-CoA desaturase (SCD) enzyme by the HCV replication machinery and in cancer cells may lead to an increased production of monounsaturated fatty acids concomitant to decreased levels of saturated fatty acids in viral-related CLD and HCC patients [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether PA acts as a direct TLR4 ligand has been extensively challenged in recent years [119]. The first piece of evidence showing PA is not a direct agonist of this receptor was brought in by Lancaster et al, who demonstrated that PA treatment does not induce the conformational changes, dimerization nor endocytosis that characterize TLR4 active state.…”
Section: Sfamentioning
confidence: 99%